WORKING MEMORY IN THE PROCESS OF TEACHING SONGS - Medne, Dace; Vilde, Ilze (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2022)
The control processes and mnemonic strategies used in working memory are important both in the general learning process and in the music learning process. In the acquisition of music, the working memory determines the formation of auditory notions, which is an essential dimension in the development of musicality. Its qualitative indicators are (1) accuracy - accurate perception and reproduction of memorized music material; (2) persistence - duration of remembrance. Therefore, it is pedagogically important to improve it at the primary school age, because working memory forms the basis for creating more complex conceptual content constructions both in music and in other fields. The aim of the research is to promote the development of working memory in the process of teaching songs. In order to achieve the goal of the research, a song teaching strategy for the development of working memory has been developed, a pedagogical observation of the music learning process for a duration of three years at the primary school level has been performed, and the obtained data have been analysed using descriptive statistics. The sample of the study consists of 200 primary school students. The data obtained in the article allow us to conclude that the purposefulness and regularity with which the chosen exercises are used, the quality of music perception and attention, and musical thinking all contribute to the development of musical memory in primary school music education. The relationship between song acquisition and working memory described in this publication expands the understanding of music educators and helps them improve their professional skills.